Perbandingan Instrumen Hukum Terhadap Praktik Biopiracy Ditinjau dari Regulasi Indonesia dan India - Bintang Yusuf Hidayatullah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
Intellectual property, which is a form of human thought that a person must benefit from in the form of moral rights and economic rights, has had various forms over time. Where one of the forms of Intellectual Property is Traditional Knowledge which is an idea and ideas contained in the community that contains local value generated based on experience passed down from generation to generation. This Traditional Knowledge is widely found in countries that have a variety of ethnic groups and cultures including Indonesia and India. Because Traditional Knowledge is a form of intellectual property that must be protected by the state, a regulation / legal instrument is needed to regulate it. Also at this time there is an actual phenomenon of piracy of natural resources and Traditional Knowledge owned by local communities for commercial purposes called biopiracy. Indonesia and India have several regulations to overcome the practice of biopiracy where the two countries have different characteristics and instruments in terms of implementing the Nagoya Protocol. Although Indonesia has ratified the Nagoya Protocol, the implementation of Indonesia is still lacking in several things such as institutions, legal instruments, and inventory of Traditional Knowledge owned by Indonesia compared to the Nagoya Protocol. Although Indonesia has ratified the Nagoya Protocol, the implementation of Indonesia is still lacking in several matters such as institutions, legal instruments, and inventory of Traditional Knowledge owned by Indonesia compared to India which has been better than some of these aspects.